Phylogenomics of Tick Inward Rectifier Potassium Channels and Their Potential as Targets to Innovate Control Technologies - Saelao, Perot; Hickner, Paul V.; Bendele, Kylie G.; Pérez de León, Adalberto A. (Frontiers in Cellular and Infection Microbiology, 2021)
This study was conducted to enhance the identification of novel targets to develop acaricides that can be used to advance integrated tick-borne disease management. Drivers for the emergence and re-emergence of tick-borne diseases affecting humans, livestock, and other domestic animals in many parts of the world include the increased abundance and expanded geographic distribution of tick species that vector pathogens. The evolution of resistance to acaricides among some of the most important tick vector species highlights the vulnerability of relying on chemical treatments for tick control to mitigate the health burden of tick-borne diseases. The involvement of inward rectifier potassium (Kir) channels in homeostasis, diuresis, and salivary gland secretion in ticks and other pests identified them as attractive targets to develop novel acaricides. However, few studies exist on the molecular characteristics of Kir channels in ticks. This bioinformatic analysis described Kir channels in 20 species of hard and soft ticks. Summarizing relevant investigations on Kir channel function in invertebrate pests allowed the phylogenomic study of this class of ion channels in ticks. How this information can be adapted to innovate tick control technologies is discussed.